2021
DOI: 10.1080/14786419.2021.1974437
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and chemical profiling of the Red Sea soft coralsLitophyton arboreum

Abstract: The objective of this research was to evaluate the cytotoxic activities of the fractions and isolated compounds of the soft corals Litophyton arboreum against A549, MCF-7 and HepG2 cell lines by MTT assay method, and to chemically investigate the various metabolites of its total extract using LC-HR-ESI-MS metabolomic profiling. The metabolomic profiling revealed the presence of various metabolites, mainly sesquiterpenes and steroids reported for the first time in L. arboreum.Additionally, eight compounds (1-8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…The values 285.21, 303.21, 225.21, and lastly 199.17 are all consistent with the fragments [M + H-C 5 H 10 O-H 2 O] + , [M + H-C 5 H 10 O] + , [C 17 H 20 + H] + , and [C 15 H 18 + H] + , respectively. These outcomes were supported by the findings reported by [ 73 , 74 ].…”
Section: Discussionsupporting
confidence: 91%
“…The values 285.21, 303.21, 225.21, and lastly 199.17 are all consistent with the fragments [M + H-C 5 H 10 O-H 2 O] + , [M + H-C 5 H 10 O] + , [C 17 H 20 + H] + , and [C 15 H 18 + H] + , respectively. These outcomes were supported by the findings reported by [ 73 , 74 ].…”
Section: Discussionsupporting
confidence: 91%
“…The chemical and biological characteristics of L. arboreum have only been the subject of several studies [ 9 , 42 , 47 ]. Sesquiterpenes, diterpenes, and polyhydroxylated steroids are just a few of the 250 bioactive secondary metabolites that Litophyton has been found to produce.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, research on marine soft corals will result in the creation of several chemically diverse compounds with a wide range of biological activities that might be applied to the pharmaceutical business [ 7 ]; there are twenty genera in the Nephtheidae family, which is a rich source of metabolites with therapeutic use [ 8 ]. The most well-known metabolites are steroids and terpenes, which are antibacterial, anti-inflammatory, and anticancer [ 9 ]. The world’s Indo-Pacific and Red Sea regions are home to the genus Litophyton , a well-known member of the Nephtheidae family [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wu (2013) conducted a study on Echinogorgia flora and found that its sesquiterpene active ingredients showed a weak antiviral activity against influenza virus. Mahmoud et al (2022) showed that the steroids and sesquiterpene of Red Sea soft corals showed evident activity on A549, MCF-7, and HepG2 cell lines. The chemical compounds in Scleractinia ※ ( Zhao et al, 2016 ) exhibit good biological activities, such as cytotoxic, antibacterial, insecticidal, and toxic effects on fish.…”
Section: The Application and Variety Of Coral In Traditional Medicinementioning
confidence: 99%